Morphological and mechanical characterization of chitosan-calcium phosphate composites for potential application as bone-graft substitutes - van de Graaf, Guilherme Maia Mulder; de Zoppa, Andre Luis do Valle; Moreira, Rodrigo Crispim; Maestrelli, Sylma Carvalho; Marques, Rodrigo Fernando Costa [UNESP]; Campos, Maria Gabriela Nogueira (FapUNIFESP (SciELO), 2015)
Introduction: Bone diseases, aging and traumas can cause bone loss and lead to bone defects. Treatment of bone defects is challenging, requiring chirurgical procedures. Bone grafts are widely used for bone replacement, but they are limited and expensive. Due to bone graft limitations, natural, semi-synthetic, synthetic and composite materials have been studied as potential bone-graft substitutes. Desirable characteristics of bone-graft substitutes are high osteoinductive and angiogenic potentials, biological safety, biodegradability, bone-like mechanical properties, and reasonable cost. Herein, we prepared and characterized potential bone-graft substitutes composed of calcium phosphate (CP) -a component of natural bone, and chitosan (CS) -a biocompatible biopolymer. Methods: CP-CS composites were synthetized, molded, dried and characterized. The effect of drying temperatures (38 and 60 °C) on the morphology, porosity and chemical composition of the composites was evaluated. As well, the effects of drying temperature and period of drying (3, 24, 48 and 72 hours) on the mechanical properties -compressive strength, modulus of elasticity and relative deformation-of the demolded samples were investigated. Results: Scanning electron microscopy and gas adsorption-desorption analyses of the CS-CP composites showed interconnected pores, indicating that the drying temperature played an important role on pores size and distribution. In addition, drying temperature have altered the color (brownish at 60 °C due to Maillard reaction) and the chemical composition of the samples, confirmed by FTIR. Conclusion: Particularly, prolonged period of drying have improved mechanical properties of the CS-CP composites dried at 38 °C, which can be designed according to the mechanical needs of the replaceable bone.
Keywords: Bone-grafts; Calcium phosphate; Chitosan; Mechanical properties; Substitutes